BUKIT SILEH GRAPES HUB: TEKNOLOGI INOVATIF BUDIDAYA ANGGUR BERKELANJUTAN BERBASIS AGROPRENEUR DAN AGROTOURISM - Sari, Winda Purnama; Ilahi, Ayu Kurnia; Tama, Duma Putri; Nurkholifah, Nurkholifah; Batubara, M. Zidan Fernanda (Jurnal Pemberdayaan Sosial dan Teknologi Masyarakat, 2025)
Abstract: Bukit Sileh is known as an area that produces competitive high-quality vegetables in the regional market and potential to be an attractive natural tourist destination. However, there are several obstacles faced by the community, such as climate change (causing crop failure), limited quality inputs, pest and disease attacks, high operational costs and low selling prices. Therefore, efforts are needed to diversify and increase community income through grape cultivation. Grape production continues to increase but has not been able to meet domestic demand, thus providing promising business opportunities. This activity aims to improve the technical and managerial capacity of farmers and support the application of appropriate and sustainable technology. The implementation was carried out participatively in three main stages: surveying and mapping potential; training and technical assistance; and monitoring and evaluation. The results showed an increase in farmers' knowledge and skills in grape cultivation by applying greenhouse technology and drip irrigation systems with adaptive varieties. In addition, there was also an increase in understanding of marketing aspects through fruit quality testing. This activity successfully built a more professional and sustainable foundation for production and marketing to realize an independent village through the development of community-based agrotourism. Keywords: grapes, empowerment, technology, agrotourism, community service Abstrak: Bukit Sileh dikenal sebagai daerah penghasil sayuran berkualitas tinggi yang kompetitif di pasar regional dan memiliki potensi sebagai lokasi wisata alam yang menarik. Namun terdapat beberapa kendala yang dihadapi masyarakat, seperti perubahan iklim (menyebabkan gagal panen), terbatasnya input berkualitas, serangan hama dan penyakit, biaya operasional yang tinggi dan harga jual yang rendah. Maka dibutuhkan upaya diversifikasi peningkatan pendapatan masyarakat melalui budidaya tanaman anggur. Produksi anggur terus mengalami peningkatan namun belum mampu memenuhi permintaan dalam negeri, sehingga memberikan peluang usaha yang menjanjikan. Kegiatan ini bertujuan untuk meningkatkan kapasitas teknis dan manajerial petani serta  mendukung penerapan teknologi tepat guna dan berkelanjutan. Pelaksanaan dilakukan secara partisipatif dalam tiga tahapan utama: survei dan pemetaan potensi serta kebutuhan; pelatihan dan pendampingan teknis, serta monitoring dan evaluasi. Hasil kegiatan menunjukkan peningkatan pengetahuan dan keterampilan petani dalam budidaya tanaman anggur dengan menerapkan teknologi greenhouse dan sistem irigasi tetes serta varietas unggul yang adaptif. Selain itu juga terjadi peningkatan pemahaman dalam aspek pemasaran melalui pengujian mutu buah. Kegiatan ini berhasil membangun fondasi produksi dan pemasaran yang lebih profesional dan berkelanjutan untuk mewujudkan desa mandiri melalui pengembangan agrowisata berbasis komunitas. Kata Kunci: anggur, pemberdayaan, teknologi, agrowisata, pengabdian